Struktur Peranti Mental (Id, Ego, Super Ego) Pesantren dalam Intimasi dengan Lawan Jenis - Herlambang Andi Prasetyo Aji (Ilmu Psikologi Universitas Yudharta Pasuruan)
Adolescence is a period where there is a strong relationship to the opposite sex and this term is often referred to as an intimacy relationship. Intimation in the structure of mental devices is a necessity that demands to be fulfilled. Adulthood students who are in the boarding school environment in particular indirectly have to maintain their good name in the eyes of civil society as boarding school graduates especially in their relations to the opposite sex. Intimate needs are the natural instincts of adolescents but on the other hand these needs will also be fatal if those who graduate from the boarding school university are wrong in implementing them. For this reason, the researchers want to explore the dynamics of mental devices in the context of intimacy relationships, especially in Islamic boarding school-based university students. The researcher used qualitative research with a phenomenological approach. The researcher used a purposive sampling technique in determining the research subject. The method of data collection in this study used observation and in-depth interviews with four subjects. In general, the process experienced by most research subjects in overcoming the impulse that they feel, namely by using the ego self defense mechanism in the form of compensation, a mechanism that someone prefers to pursue a goal, with a more active effort in trying to overcome the lack which are actually. In short, they prefer to strengthen themselves.